AVALIAÇÃO TOXICOLÓGICA DE NANOPARTÍCULAS LIPÍDICAS SÓLIDAS DE CURCUMINA E CAPSAICINA E SEU EFEITO SOBRE A COLITE ULCERATIVA INDUZIDA QUIMICAMENTE EM CAMUNDONGOS C57BL/6 - Martins, Nára Maria Beck (2023)
Idiopathic Inflammatory Bowel Disease (IBD) is a chronic inflammatory disorder of the gastrointestinal tract related to the exacerbation of the immune response. The two most well-known types are Crohn's disease (CD) and ulcerative intestinal colitis (UC), with increasing incidence worldwide. The traditional treatment of this type of illness involves aminosalicylates, corticosteroids, and immunosuppressants, all with significant side effects and toxicity. To try to reduce the side effects of these medications, one of the strategies is using spices traditionally used in cooking that demonstrate an anti-inflammatory effect in current research. Curcumin, a polyphenol, and capsaicin, an alkaloid, stand out in publications for their anti-inflammatory power. These substances have low solubility in water and low bioavailability, so encapsulation in a nanostructure is a strategy for applicability in a biological environment. The objectives of this work were to evaluate: i) toxicological parameters of solid lipid nanoparticles of curcumin and capsaicin (NCC) and its actives, and ii) the anti-inflammatory effect of NCC in mice submitted to ulcerative colitis (UC) induced by dextran sulfate sodium (DSS). First, was evaluated the safety profile of NCC (3 mg/kg of curcumin and 0.1 mg/kg of capsaicin), active free nanoparticles called white nanoparticles (NB), and unencapsulated curcumin and capsaicin (CC) in vivo by oral administration for 7 days in twenty-four female C57BL/6 mice and hematological analyses, liver and kidney biochemical markers and histopathological changes were performed. The biochemical and histopathological parameters of the metabolizing and excreting organs did not indicate significant alterations, showing that, under the conditions of this study, CC, NB, and NCC are biocompatible and do not cause systemic toxicity. In the second part of the work, thirty-two female C57BL/6 mice were subjected to experimental UC by adding 5% DSS to their water bottles. Mice were divided into four groups: Vehicle (VE), UC (DSS 5%), UC plus sulfasalazine (UC+S, 50 mg/kg), and UC plus NCC. Mice were treated with sulfasalazine or NCC by gavage for seven days. After treatment, the animals were evaluated for pyruvate kinase (PK) activity and expression, TNF-α levels, and histopathological parameters. Results showed that UC induced inflammation in the colon, and sulfasalazine effectively reduced tissue damage. However, NCC did not have the same protective effect as sulfasalazine. UC also affected PK activity in the colon and brain, and NCC only protected against the effect of UC on brain PK activity. The study concluded that the nanostructures practically did not change the toxicological parameters, the changes in PK activity induced by UC seem to be associated with PKM2 expression, and sulfasalazine was more effective than NCC in protecting against histopathological changes in UC.